APLIKASI SISTEM INFORMASI PINJAMAN PADA KOPERASI CITRA ABADI MALANG BERBASIS WEB - Sofyan Zainuri; Dwi Safiroh Utsalina (Sekolah Tinggi Manajemen Informatika & Komputer PPKIA Pradya Paramita Malang, 2024)
Citra Abadi Cooperative is a cooperative engaged in savings and loans with the province of East Java Permit No. : 518 / BH / 36/103/2002 of July 31, 2002, located at Jalan S.Supriadi 32D Breadfruit Malang. Cooperative Citra Abadi originally consisted of twenty people that all members are employees themselves who have the vision to make the leading credit unions and quality in the service of micro and small enterprises. A vision that makes Cooperative Citra Abadi intend to renovate its information system for the better. From the results of the analysis showed that there are some new parts in the organizational structure Cooperative Citra Abadi that require computer-based processes and in this section is proposed to design computer-based information systems.